Osteoporosis drug treatment: duration and management after discontinuation. A position statement from the Swiss Association against Osteoporosis (SVGO/ASCO) (Swiss Medical Weekly, 2017)
Antiosteoporotic drugs are recommended in patients with fragility fractures and in patients considered to be at high fracture risk on the basis of clinical risk factors and/or low bone mineral density. As first-line treatment most patients are started with an antiresorptive treatment, i.e. drugs that inhibit osteoclast development and/or function (bisphosphonates, denosumab, oestrogens or selective oestrogen receptor modulators). In the balance between benefits and risks of antiresorptive treatment, uncertainties remain regarding the optimal treatment duration and the management of patients after drug discontinuation. Based on the available evidence, this position statement will focus on the long-term management of osteoporosis therapy, formulating decision criteria for clinical practice.